2012
DOI: 10.1021/om300711c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Copper(I) Thiolate Complexes in the Thioetherification of Aryl Halides

Abstract: The copper(I) thiophenolato complexes 1–3 containing 1,10-phenanthroline (phen) and 2,9-dimethyl-1,10-phenanthroline (Me2phen) were isolated in excellent yields from reactions of [CuOtBu]4 with the dative ligands and subsequent addition of 1 equiv of arylthiol and characterized spectroscopically. X-ray structural analysis of a single crystal of [(phen)Cu(µ-SC6H5)]2 (1) revealed that this complex adopts a neutral dimeric form with a weak Cu–Cu bonding interaction. These complexes were found to react with iodoar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 53 publications
4
57
0
Order By: Relevance
“…The Gibbs energies computed for the formation of the complexes [(phen)Cu I (XPh)] follow the trend according to the pK a of the nucleophiles, i.e., pK a (PhNH 2 ) = 27.0, pK a (PhOH) = 9.95, and pK a (PhSH) = 6.5. In concordance with the experiments outcomes [60,65] [66,67], Chen et al [42], and Zhang et al [59][60][61]. Our results show that this disproportionation is unfavorable in nonpolar solvents while it becomes favored when the dipolar constant of the solvent increases, in good agreement with previously reported results [59][60][61].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The Gibbs energies computed for the formation of the complexes [(phen)Cu I (XPh)] follow the trend according to the pK a of the nucleophiles, i.e., pK a (PhNH 2 ) = 27.0, pK a (PhOH) = 9.95, and pK a (PhSH) = 6.5. In concordance with the experiments outcomes [60,65] [66,67], Chen et al [42], and Zhang et al [59][60][61]. Our results show that this disproportionation is unfavorable in nonpolar solvents while it becomes favored when the dipolar constant of the solvent increases, in good agreement with previously reported results [59][60][61].…”
Section: Resultssupporting
confidence: 93%
“…The Cu-NHPh bond distance is within the range of distances reported for the Cu I -amido complexes (~1.865 Å). As expected, the Cu-O and Cu-S bond distances are shorter than those found for the dimer, i.e., 2.066 Å [66] and 2.340 Å [42] for Cu-O and Cu-S bonds, respectively. Additionally, the Cu-S distance is also slightly longer than those measured by Kaim and co-worked for thiolate copper complexes (ca.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…23 Later, studies of our own also confirmed that for Ullmann O-arylation of phenols with aryl bromides a similar bromine atom transfer mechanism is the most favored among several commonly proposed mechanisms. 24 As to the S-arylation mechanism, there is one experimental study concerning the preparation and reactivity studies of a few Cu(I)-thiophenolato complexes reported by Weng and Hartwig et al 25 Cheng et al reported an ESI-MS study that characterized several Cu-thiolate intermediates during the Ullmann S-arylation reaction developed by Venkataraman et al 26 However, the mechanism is still vague and elusive. Up to now, Ullmann S-arylation has generally escaped detailed computational study.…”
Section: Introductionmentioning
confidence: 99%